Effect of Re-engineering Business Administrative Processes in Improving the Productive Efficiency of the Yemen Textile Corporation-Sana’a - Moftah, Mohammed Hussein Ali; Alsanfi, Abdullah Abdullah (The Arab Journal of Administration, 2025)
This study aimed to identify the impact of Business Process Reengineering in its dimensions (The organizational and administrative factors dimension, the human factor dimension, and the technical factor dimension), on the level of improving production efficiency on the General Corporation for Textile industry – Sana’a. The researcher employed the quantitative approach, using both descriptive and analytical methods. Therefore, a questionnaire was designed to collect data toward the study’s objectives. Accordingly, a sample of (279) employees of the General Corporation for Textile Industry was selected using the stratified random sampling method while SPSS software was used as a tool to analyze the collected data. The study concluded that the BPR overall degree in the General Corporation for Textile industry is medium and close to the low level, with an average of (2.9285). Additionally, the results also showed that the level of production efficiency improvement is medium with an average of (3.0185). Moreover, the results indicated that there is a positive and statistically significant impact of BPR on improving the production efficiency, and this is evident through the dimensions of BPR in terms of organizational, administrative, human and technical factors since it was found that there is a positive impact of statistical significance for these factors. The study presented recommendations, the most important of which are:: Forming a technical and scientifical specialized team and empowering them to implement the methods of BPR and work to define the targeted visions in the overall reconstruction of the institution (legally / organizationally / structurally / administratively / financially / technically / commercially). This will help address technical weaknesses and enhance the development of the size, energy capabilities and production efficiency of the institution.